Guide for Road Safety Interventions : Evidence of What Works and What Does Not Work - Turner, Blair; Job, Soames; Mitra, Sudeshna (World Bank, Washington, DC, 2021)
This guide provides advice on 'What Works and What Does Not Work' in road safety, with a focus on interventions that can be used by those working in low- and middle-come countries (LMICs). While the intended audience is primarily those working in LMICs, it is likely that the information will be of relevance in all countries. The contents will be valuable to those working on road safety at the policy or practitioner level, including World Bank Technical Team Leaders and those in client countries seeking to establish or expand road safety programs. The guide introduces the topic of road safety interventions, a summary of findings, and references for more detailed information. The document sets knowledge within a ‘Safe System’ context and highlights the need for an evidence-based approach across Safe System components. At the core of this guide is a summary table with an overview of beneficial and nonbeneficial interventions. This is supported in an appendix with more detailed information, including case studies and reference to the evidence base to support the summary. In this guide, effective interventions are defined as those that reduce fatal and serious injuries. The most effective interventions are those that substantially reduce or eliminate these injuries. Ineffective interventions therefore are those interventions that do not reduce these injuries. The focus of the guide is on intervention effectiveness in terms of this fatal and serious injury reduction, and not on issues such as cost, public acceptability, period of benefit (treatment or service life), or related issues. Although intervention effectiveness should be a main driving force when selecting road safety solutions, these other issues also need to be considered. For example, an economic analysis comparing the costs for interventions and their likely benefits (or savings in crash costs) is important to ensure that interventions are cost-effective and that limited resources are invested in the most beneficial solutions. Information has not been provided on this aspect of effectiveness in this guide as this analysis is context specific (for instance, the cost of interventions may vary substantially between countries or even different road environments within a country).